A Comparative Study of Health and Hygienic Practices Among Different Types of Professional Students: A Comparative Analysis of Health and Hygienic Practices among Professional Students (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The purpose of the study was tocompare the health and hygienic practices among different types ofprofessional. The total number 150 subjects were selected randomly for studyfrom different professional institute, age group only 18 to 25 years. The investigator prepared aquestionnaire comprising of 20 statements based on health and hygienicpractices and subject were asked to give their opinion in Yes/No. Thequestionnaire was distributed to 150 subjects and all 100% of them returned thecompleted questionnaire were received. Descriptive technique of percentage wasapplied to know the responses of the students. The responses had indicated thata majority of professional student’s namely physical education, law andmanagement have their positive health and hygienic practices.